2014
DOI: 10.1515/sg-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and Genetic Diversity in Wild Apple (Malus sylvestris (L.) MILL.) from Various Regions in Germany and from Luxembourg

Abstract: Malus sylvestris is the only apple species native to Central Europe. Its genetic integrity may be threatened by hybridization with the cultivated apple (Malus × domestica). A total of 883 genotypes, 477 putative wild apples in Germany and Luxembourg and 406 old to modern cultivars has been investigated. Wild apples growing in Germany originated from Rhineland-Palatinate, North Rhine-Westphalia, Saxony-Anhalt and Saxony. The genetic structure was analysed at ten isozyme marker loci, and morphology was studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
4
20
1
1
Order By: Relevance
“…A higher threshold can result in the misclassification of hybrids as pure and a lower threshold might have the opposite effect and identify a sample as hybrid when it is actually pure. In previous Malus studies values of P ≤0.1 (Cornille et al, 2013b;Cornille et al, 2015), P ≤0.15 (Larsen et al, 2006) and P ≤0.2 (Coart et al, 2006;Wagner et al, 2014;Feurtey et al, 2017) sylvestris and samples with P dom ≥0.85 and P dom ≥0.80 as pure M. domestica. The threshold for the other classes stayed the same apart from the backcross boundaries being adjusted to reflect the altered threshold for purity.…”
Section: Statistical Analysesmentioning
confidence: 85%
See 1 more Smart Citation
“…A higher threshold can result in the misclassification of hybrids as pure and a lower threshold might have the opposite effect and identify a sample as hybrid when it is actually pure. In previous Malus studies values of P ≤0.1 (Cornille et al, 2013b;Cornille et al, 2015), P ≤0.15 (Larsen et al, 2006) and P ≤0.2 (Coart et al, 2006;Wagner et al, 2014;Feurtey et al, 2017) sylvestris and samples with P dom ≥0.85 and P dom ≥0.80 as pure M. domestica. The threshold for the other classes stayed the same apart from the backcross boundaries being adjusted to reflect the altered threshold for purity.…”
Section: Statistical Analysesmentioning
confidence: 85%
“…Not only has this led to discussions whether genuine wild M. sylvestris still exists today (Henning, 1947;Remmy and Gruber, 1993;Wagner, 1996) but has also raised concerns about the genetic integrity of wild apple. This has recently sparked a number of studies which investigated the extent of hybridisation between the two apple species in Europe using molecular markers (Coart et al, 2003(Coart et al, , 2006Larsen et al, 2006;Schnitzler et al, 2014;Wagner et al, 2014;Cornille et al, 2015;Feurtey et al, 2017). Although results varied between studies the overall picture emerged that hybrids may occur at significant frequencies in wild apple populations (7% to 36%, Cornille et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…“It is now fairly certain that rice evolved in this manner, with Indica rice evolving because of hybridization”, Purugganan explained. “Apples are also a very good example , and we have a paper in review that indicates date palms also benefited from interspecific hybridization”.…”
Section: The Beginning Of Domesticationmentioning
confidence: 99%
“…Son codominantes y su principal desventaja es que están limitados por el bajo número de encimas disponibles y por tanto la resolución de la diversidad es limitada (Mondini et al 2009). Han sido usados desde 1970 para analizar la diversidad genética de plantas (Brown 1978) y, por tanto, también de árboles frutales como muestran algunos trabajos recientes en manzano (Wagner et al 2014), avellano (Leinemann et al 2013) o madroño (Takrouni et al 2012 , Ellegren 2004, Parida et al 2009). Se han propuesto varios modelos de mutación para las secuencias microsatélites como el modelo de alelos infinitos (Infinite Allele Model) (IAM), el de mutación paso a paso (Stepwise Mutation Model) (SMM), o el de formación de un número k de alelos (K-Allele Model) (KAM).…”
Section: Marcadores Moleculares Para La Medida De La Diversidad Genéticaunclassified
“…They are codominant, and their main disadvantage is that the number of available enzymes is limited and, thus, their power to analyze diversity is reduced (Mondini et al 2009). They have been used since the 1970s to analyze genetic diversity in plants (Brown 1978), but they can still provide valuable information for diversity studies in fruit trees shown in some recent works in apple (Wagner et al 2014), hazelnut (Leinemann et al 2013), or Arbutus unedo (Takrouni et al 2012). DNA-based markers, commonly known as molecular markers, have been continuously developed since the 1980s and can be associated or not to a functional trait; they can, in general terms, be classified into dominant (such as RAPDs or AFLPs) or codominant (such as RFLPs, microsatellites, or SNPs) markers depending on whether heterozygous and homozygous genotypes can be distinguished.…”
Section: Main Types Of Molecular Markers Used In Genetic Diversity Anmentioning
confidence: 99%